Supporting Open Science Data Curation, Preservation, and Access by Libraries - Eric L Olson; Nicole Pfeiffer; Claire Riss; Jefferson Bailey; Lori Donovan (Open Science Framework, 2022)
In this webinar, attendees will learn about both the technical and practical aspects of this collaborative project connecting the researcher tool OSF and the preservation system of Internet Archive. We will demonstrate how researchers can improve the openness and reproducibility of their research through preregistration, and how those preregistrations are preserved with Internet Archive. We will answer questions and seek to learn your needs and use cases for how this powerful workflow can support library curation and stewardship of open research.